2018
DOI: 10.1155/2018/3463724
|View full text |Cite
|
Sign up to set email alerts
|

Study of Isothermal, Kinetic, and Thermodynamic Parameters for Adsorption of Cadmium: An Overview of Linear and Nonlinear Approach and Error Analysis

Abstract: Reports about presence and toxicity of Cd2+ in different chemical industrial effluents prompted the researchers to explore some economical, rapid, sensitive, and accurate methods for its determination and removal from aqueous systems. In continuation of series of investigations, adsorption of Cd2+ onto the stem of Saccharum arundinaceum is proposed in the present work. Optimization of parameters affecting sorption potential of Cd2+ including pH, contact time, temperature, sorbent dose, and concentration of sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(140 citation statements)
references
References 41 publications
4
132
0
4
Order By: Relevance
“… 51 The negative values of Δ G° indicated that the adsorption mechanism of MB onto the CNC/ZnO nanocomposite was a favorable spontaneous process. According to some studies, 52 , 53 a value of enthalpy Δ H ° < 84 kJ/mol represents physisorption while the values between 84 and 420 kJ/mol are considered to be chemisorption. Therefore, it is an indication that the interaction mechanism for the sorption of MB onto CNC/ZnO could be chemical interaction.…”
Section: Resultsmentioning
confidence: 99%
“… 51 The negative values of Δ G° indicated that the adsorption mechanism of MB onto the CNC/ZnO nanocomposite was a favorable spontaneous process. According to some studies, 52 , 53 a value of enthalpy Δ H ° < 84 kJ/mol represents physisorption while the values between 84 and 420 kJ/mol are considered to be chemisorption. Therefore, it is an indication that the interaction mechanism for the sorption of MB onto CNC/ZnO could be chemical interaction.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of adsorption studies, the Langmuir isotherm was found to be the most suitable for the heavy metals according to the R 2 value. Therefore, only this isotherm model was used for the calculation of error functions (ErF) 47,48 . The results of the error functions are presented in Table 3.…”
Section: Adsorption Isotherm and Kinetic Models In This Study The Lmentioning
confidence: 99%
“… E=12kadThe parameter k ad obtained from the slope of the model plot is reported in Table 4. Since the value k ad is greater than 8 kJ⋅mol −1 56 for both adsorbents, their adsorption processes are chemical. The predicted equilibrium capacities by these models versus equilibrium pressure compare with the experimental data in Fig.…”
Section: Resultsmentioning
confidence: 99%